(untitled) (Jurnal Akuntansi dan Keuangan, 2011)
This research is a classroom action research. The goal of conducting this research is to improve students’ enjoyment level and their test scores by implementing role-playing method. The research is conducted in Accounting Education Study Program of Sanata Dharma University at odd semester on academic year 2010/2011. The participants were divided into two classes. The first class was the class that got the treatment, while the second class was the control class. The result of the study showed that there was an improvement of students’ enjoyment level and test scores in the class which implemented role-playing method.